Clonal Propagation Potential of some Selected CPTs of Neem (Azadirachta indica A. Juss) from Three Provenances of Orissa - Bhola, N. (Indian Forester, 2004)
Clonal propagation potential of 15 CPTs (Candidate Plus Trees) of Neem (Azadirachta indica A. Juss) located in three different provenances of Orissa viz. Bolangir , Bhwanipatna and Khurda provenance were tested in mist chamber at the Department of Forestry , Orissa University of Agriculture and Technology , Bhubaneswar. The propagation potential of branch cuttings of different CPTs differed significantly in terms of shoot development , root development and survival. At the age of 60 days of planting of cuttings the relative propagation potential of different CPTs was observed in the order of : BLG -1 > BLG-6 > BLG-7 > KPK-2 > KPK-4 in Bolangir provenance while BPN-5 > BPN-11>BPN-14> BPN-16 > BPN-15 in Bhwanipatna provenance and KHD-l > KHD-9 > KHD-6 > KHD-5> KHD-8 in Khurda provenance. Among the CPTs , BLG-l excelled over others and among the provenances Bolangir was observed to be most promising one.